Fundamental Studies On The Mechanism Of Polyalthia longifolia (Sonn.) Thwaites Polyphenols Action In Hela Cells In Relation To Microrna Regulation - Soundararajan, Vijayarathna (2017)
Polyalthia longifolia (Sonn.) Thwaites is a lofty, evergreen tree that extensively known for its medicinal beneficial in treating various ailments. Though P. longifolia ethnomedicinal benefits had been recognised, studies concerning its anticancer and apoptotic cell death activity in relation to microRNAs (miRNA) and their mechanism had never been studied in detail. Herein, this study was conducted to comprehensively study these characteristics.